Neonatal Abstinence Syndrome: Twins Case Series - Pandey, Rajesh; Pandey Sapkota, Narmada; Kumar, Deepak (Frontiers in Pediatrics, 2017)
Background: Use or abuse of opioids and related drugs during pregnancy increases the risk of maternal and neonatal morbidities, including increased susceptibility to Neonatal Abstinence Syndrome (NAS). Severity of NAS is determined by both environmental and genetic factors, but the level of influence each one of them has in determining the severity of NAS is not fully understood. Since the incidence and severity of NAS varies a lot among susceptible infants, twin studies might give us valuable insights into understanding the relative roles of environmental and genetic factors at the onset of the disease and during its progression. Higher concordance of occurrence and severity of NAS in monozygotic twins compared to dizygotic twins would suggest a genetic role in the pathogenesis of NAS. However, comparable concordance suggests a non-genetic or an environmental basis. In this case series, we report neonatal outcomes including severity of NAS among monozygotic and dizygotic twins. Methods: A retrospective chart review was performed for all newborn twins who were at risk of developing NAS, were born in our institution between January 2006 and December 2014, and had a gestational age of, or greater than, 30 weeks. Results: During the study period, we identified seven sets (total of 14 infants) of eligible twins, which comprised of six dizygotic and one monozygotic twins, from a total of 550 infants who were at risk of developing NAS. Among the seven sets of twins, two sets were concordant for severe NAS and required pharmacological management, three sets of twins were concordant in not having severe NAS and did not require pharmacological management, and the remaining two sets were discordant, where one of the twins required pharmacological treatment. Conclusion: Five out of the seven sets of twins in our study exhibited concordance and two sets showed discordance in withdrawal severity. Larger studies may help in understanding the roles of genetic and environmental factors in determining the severity of NAS.